Bone marrow stem cells: current and emerging concepts. (January 2015) - Méndez‐Ferrer, Simón; Scadden, David T.; Sánchez‐Aguilera, Abel
Abstract : The interactions of stromal cells with hematopoietic cells in the bone marrow have long been a subject of research, but only recently have technologies allowed us to dissect them at the stem cell level. On the other hand, limitations of these technical tools might explain numerous discrepancies in this field. It is becoming increasingly clear that mesenchymal stem cells (MSCs) represent an important component of the hematopoietic stem cell (HSC) niche in the bone marrow. However, there is heterogeneity among HSCs, and many putatively different mesenchymal progenitors identified in the bone marrow using Cre recombinase–driven mouse lines seem to exhibit HSC niche properties. Development of better reporter lines has demonstrated that some of these Cre lines do not always specifically mark the expected cells. Also, characterization of different cell populations has often been partial, and issues of redundancy and compensation might explain apparently contradictory results. Recognizing and overcoming these limitations, while also clearly defining the distinctions between subgroups of mesenchymal cells, will be essential to advance the field.